Attraction and Word Of Mouth In A Visit Decision - Tri Palupi Robustin (Jurnal Ilmu Manajemen Advantage, 2020)
The purpose of this study was to determine the partial and simultaneous influence between attractiveness and word of mouth on the decision to visit Watu Ulo Beach in Jember Regency. The purpose of this study is explanatory (explanatory research) and predictions where explanatory research is a type of research that explains the causal relationship between one variable with other variables through hypothesis testing. The research population is tourists visiting Watu Ulo Beach. The sampling technique used is purposive sampling. The analysis used in this study is a multivariate analysis, namely, multiple linear regression analysis consisting entirely of 3 (three) variables. The number of samples in this study was 60 sample members. The results of this study indicate that the attractiveness and word of mouth influence partially and simultaneously on the decision to visit Watu Ulo Beach. The results of the multiple determination coefficient (R2) of 0.558, this means that 55.8% of the visiting decision changes are influenced by the attractiveness and word of mouth variables while the remaining 44.2% is caused by other factors of promotion, service quality, an image of tourist attraction, and others not included in the regression equation created.